From Recognition to Logical Deduction: Assessing the van Hiele Levels of Geometric Thinking Among Students of Diverse Disciplines - Markus Palobo; Nasruddin; Yonarlianto Tembang; Oswaldus Dadi (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
This study investigates the geometric thinking levels of university students using the van Hiele model as an analytical framework. A total of 85 students from four academic programs—Mathematics Education, Primary School Teacher Education, Agricultural Science, and Informatics Engineering—at Universitas Musamus participated in the study. The Van Hiele Geometry Test (VHGT), consisting of 25 multiple-choice items across five cognitive levels, was administered. Data were analyzed using descriptive statistical methods, including percentage distribution and level classification based on students’ mastery of at least three out of five items at each van Hiele level. In addition, an item-based diagnostic analysis was conducted to identify patterns of misconceptions in students’ responses. Comparative analysis across academic programs and gender was also performed to examine subgroup differences. The results revealed that most students were operating at the lower levels of geometric thinking: Level 0 (Pre-recognition), Level 1 (Visualization), and Level 2 (Analysis). Only two students reached Level 3 (Informal Deduction), and none achieved higher levels. Diagnostic findings indicated persistent misconceptions, particularly reliance on visual prototypes and difficulties in property-based reasoning. These findings highlight the need for instructional strategies aligned with students’ cognitive levels to promote higher-order geometric reasoning. This study contributes to the literature by providing insights into cross-disciplinary differences in geometric thinking at the tertiary level.